2017
DOI: 10.1016/j.enpol.2017.01.049
|View full text |Cite
|
Sign up to set email alerts
|

Open innovation in the power & energy sector: Bringing together government policies, companies’ interests, and academic essence

Abstract: The Power and Energy (P&E) sector needs to respond to several challenges fostering investments in research and development. According to the Open Innovation (OI) paradigm, key stakeholders like utilities, vendors, laboratories, universities etc. should take advantage of external knowledge to improve their innovation performance. Several studies have demonstrated that firms adopting the OI paradigm are more likely to innovate. Despite the interest of P&E firms in enhancing their innovation capabilities, surpris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
75
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(75 citation statements)
references
References 71 publications
0
75
0
Order By: Relevance
“…Besides, fuzziness (UT2) and subjectiveness (UT4). The remaining two types of uncertainty, UT1-Random uncertainty (e.g., [183,214]) and UT3-Grey uncertainty (e.g., [19,88]) are less treated by researchers in strategic EPDM (11% and 16%, respectively). Therefore, in most case studies, the uncertainties have been handled throughout (1) fuzzy linguistic (38%) or (2) fuzzy (23%) decision-making environments while considering other types of preferences' representation (e.g., intervals [199,215], intuitionistic [111,197], or trapezoidal fuzzy numbers [41]).…”
Section: Results and In-depth Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Besides, fuzziness (UT2) and subjectiveness (UT4). The remaining two types of uncertainty, UT1-Random uncertainty (e.g., [183,214]) and UT3-Grey uncertainty (e.g., [19,88]) are less treated by researchers in strategic EPDM (11% and 16%, respectively). Therefore, in most case studies, the uncertainties have been handled throughout (1) fuzzy linguistic (38%) or (2) fuzzy (23%) decision-making environments while considering other types of preferences' representation (e.g., intervals [199,215], intuitionistic [111,197], or trapezoidal fuzzy numbers [41]).…”
Section: Results and In-depth Analysismentioning
confidence: 99%
“…(3) Last, this period has been the most remarkable wherein 6 papers are identified [81,109,170,181,203,214]. Firstly, Maté et al [181] explored the opportunities to adopt more intelligent ways of managing existing RES.…”
Section: Results and In-depth Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Open innovation tools include online innovation challenges and smart IP management, where the knowledge peripheral to the main protected product is more openly shared. While the open innovation approach has yet to be more fully explored in the energy sector, and its potential benefits or drawbacks have yet to be analysed, a recent study identified likely drivers of open innovation adoption in the energy sector 5 . These drivers could include economic slow-down and risk aversion.…”
mentioning
confidence: 99%